Hubungan Karakteristik, Akses dengan Pemanfaatan Posyandu Lansia - Mertha, I Made; Suardana, I Ketut; Wedri, Ni Made; Ngurah, I Gusti Ketut Gede (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2025)
Elderly Posyandu is a health service program aimed at improving the welfare of the elderly. The utilization of Elderly Posyandu by the elderly has not been optimal until now. This study aims to determine the relationship between characteristics and access with the utilization of Elderly Posyandu. This study is a descriptive correlation study with a cross-sectional approach. The number of samples is the total sampling of respondents who meet the predetermined inclusion criteria, namely 160 samples. Data collection with questionnaires from November 11, 2024 to December 9, 2024. Data analysis was carried out using the sperm rank correlation test. The results of the study showed that most of the elderly were in the 61-70 year age group (59,4%), most of the gender was female (61,9%), most of the education level was high school (23,1%), and most of the elderly were actively working (53,1%). The support of the elderly's family was mostly in the high category (91,3%). All elderly (100%) stated that access to elderly Posyandu was easy. The utilization of elderly Posyandu was mostly in the high category, namely 153 people (95,6%). Statistical test obtained p value for age (0,000), gender (0,165), education level (0,000), occupation (0,664), family support (0,003), and access (0,725). It was concluded that only age, education level, and family support of the elderly were related to the utilization of the elderly posyandu. Elderly cadres are advised to increase motivation in the elderly to utilize the elderly posyandu to maintain health status.